In Vitro ACE Inhibitory Activity and Bioactive Compounds of Aqueous Extract of Citrus amblycarpa - I Gusti Ayu Wita Kusumawati; I Made Wisnu Adhi Putra; Ida Bagus Agung Yogeswara (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Citrus amblycarpa contain flavonoid-rich compounds and play important role in suppressing the conversion of angiotensin-converting enzyme 1 (ACE 1) to angiotensin-enzyme 2 (ACE 2). This study aimed to determine the bioactive compounds in the lime peel extract and their ability as in vitro ACE inhibitor activity. The lime peel extract was obtained by boiling the dried peel and dried leaves for 7 min at 70oC. The bioactive compound of the peel and the leaves were compared. The total phenolic, quercetin, rutin, and GABA were further quantified using spectrophotometer UV vis. The aqueous extract of C. ambylcarpa peel showed a high concentration of phenolic, quercetin, rutin, and GABA than that of the leaves extract. Furthermore, the peel extract at low concentration (0.0001 g/mL) has high efficiency in inhibiting ACE activity up to 133%. It can be concluded that the peel of C. amblycarpa is a good candidate for the management of hypertension.